Demography and regeneration of oaks in the foothill woodlands of central California: a review of the scientific literature - Tyler, C. M.; Kuhn, W.; Davis, F. W. (Quarterly Review of Biology, 2006)
We review published studies on the demography and recruitment of California oak trees and focus on the widespread dominant species of the foothill woodlands, Quercus douglasii, Q. lobata, and Q. agrifolia, to ascertain the nature and strength of evidence for a decline in populations of these species. The vast majority of studies have been of short duration (less than three years), focused on the acorn and seedling life stages, and conducted at few locations within each species’ geographic range. We summarize the extensive body of research that has been conducted on the biological and physical factors that limit natural seedling recruitment of oaks. The oak “regeneration problem” has largely been inferred from current stand structure rather than by demographic analyses, which in part reflects the short-term nature of most oak research. When viewed over longer periods of time using field surveys or historical photos, the evidence for a regeneration problem in foothill oaks is mixed. Q. douglasii shows very limited seedling or sapling recruitment at present, but longer term studies do not suggest a decline in tree density, presumably because rare recruitment is sufficient to offset low rates of mortality of overstory individuals. Q. agrifolia appears to be stable or increasing in some areas, but decreasing in areas recently impacted by the disease Phytophthora ramorum. Evidence from the few available studies is more consistent in suggesting long-term declines in foothill populations of Q. lobata. Longterm monitoring, age structure analysis, and population models are needed to resolve the current uncertainty over the sustainability of oak woodlands in California.
Keywords: oak woodland; Quercus; seedling establishment